CODE MIXING PHENOMENON IN MICRO TEACHING CLASS BY EFL STUDENTS IN GIVING SUGGESTION TO THE TRAINEE: A SOCIOLINGUISTICS STUDY - Zulianti, Hajjah (LPPM STKIP PGRI Bandar Lampung, 2013)
This research entitle code mixing phenomenon in micro teaching class by EFL students in giving suggestion to the trainee: a sociolinguistics study is aimed to describe the form of code mixing, the position of code mixing in a sentence, the language which is mixed, and the reason of mixing a code. This research is qualitative research. In this research, the writer uses recording method and writing technique in collecting the data. To analyze the data, the writer uses description technique. The result of the research shows that code mixing phenomenon occurs in the form of words, phrases, and sentences. The positions of code mixing are in the beginning, middle, and in the end of the sentence. The language which is mixed by the observers is Indonesian, and there are three reasons of mixing a code, those are to express the emotion, to emphasize the important point of the suggestion, and to have a sense of humor.